Exploring creative risk-taking and productive failure in classroom practice. A case study of the perceived self-efficacy and agency of teachers at one school. (December 2021) - Creely, Edwin; Henriksen, Danah; Crawford, Renée; Henderson, Michael
Highlights: Creativity, risk-taking and productive failure are an important part of effective teaching and learning across disciplines. Teacher perceived self-efficacy is pivotal to the implementation of risk-taking and productive failure as part of learning in classrooms. Teacher perceived self-efficacy needs to be supported and sustained through a whole school approach that addresses barriers to implementation. Abstract: There is an emerging body of research about the importance of creative risk-taking and productive failure in classroom teaching across discipline areas. However, teachers' confidence in engaging with these pedagogical ideas in their classrooms can be inhibited by perceived barriers, such as assessment demands, expectations by administrators, and the orchestration of technologies in a meaningful way. This article reports a case study in a private school in Melbourne, Australia. Six teachers experimented with risk-taking and productive failure through digital technologies in their Year 8 classes across different discipline areas. This paper examines the beliefs of these teachers about their creative capacity to enact these pedagogical ideas with technology. Using Albert Bandura's ideas of self-efficacy beliefs, mastery experiences and self-appraisal and adaptations, this study investigates the sense of agency that teachers experienced in exploring these ideas in their classrooms. Findings indicate that teachers believed that risk-taking and productive failure are important, but they experienced internal and external barriers to implementing these ideas, especially in regard to the use of digital technologies, managing student apprehension and designing learning that includes risk-taking and productive failure.